PENGARUH DIGITAL MARKETING DAN HARGA TERHADAP MINAT BELI SENTRA WISATA KULINER WIYUNG - Sukamto, Dinda Dwi Lukita; Cahya, Septyan Budy (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
Digital marketing is a marketing activity that is currently being developed and has the potential to getcustomers online through internet media. While the price is the amount of money issued in exchange to get aproduct or service that is in accordance with what we want. From the results of previous research it is known thatdigital marketing and price have a positive effect on buying interest. So the purpose of this study is to determinethe effect of digital marketing and price on buying interest in the Wiyung Culinary Tour Senta. This research isa quantitative study using a simple random sampling technique, namely by analyzing the effect of digitalmarketing (X1) and price (X2) on buying interest (Y) at the Wiyung culinary tourism center, with a total of 100subjects. Data collection techniques in this study used observation, interviews, and questionnaires. From theresults of data processing in the research, The results of the t test stated that digital marketing had an influenceon buying interest in the Wiyung culinary tourism center, prices had an effect on buying interest on the Wiyungculinary tourism center.